2012
DOI: 10.1002/glia.22373
|View full text |Cite
|
Sign up to set email alerts
|

Multiple P2Y subtypes in spinal microglia are involved in neuropathic pain after peripheral nerve injury

Abstract: A prominent signaling pathway in the development of neuropathic pain involves ATP acting on microglial purinergic receptors. Among the P2Y metabotropic receptors, we reported before that the P2Y12 receptor is upregulated in microglia following nerve injury and involved in the phosphorylation of p38 MAPK, and in the development of pain behavior. In this study, we examined the expression of P2Y6, P2Y13, and P2Y14 receptors in the spinal cord and whether these receptors are involved in the pathogenesis of neuropa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
100
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(110 citation statements)
references
References 52 publications
8
100
0
Order By: Relevance
“…In fact, not only mRNA for P2Y 12 , but also for P2Y 6,13,14 are up-regulated in microglia in the ipsilateral spinal cord following nerve injury, and a mixture of P2Y 6 , P2Y 12 and P2Y 13 selective antagonists showed a longer suppressive effect on pain behavior than did single treatments alone [75].…”
Section: Spinal Cord Microglia and Astrocytesmentioning
confidence: 97%
“…In fact, not only mRNA for P2Y 12 , but also for P2Y 6,13,14 are up-regulated in microglia in the ipsilateral spinal cord following nerve injury, and a mixture of P2Y 6 , P2Y 12 and P2Y 13 selective antagonists showed a longer suppressive effect on pain behavior than did single treatments alone [75].…”
Section: Spinal Cord Microglia and Astrocytesmentioning
confidence: 97%
“…Its activation confers neuroprotection in several ways: the promotion of neurite outgrowth, increased cell motility, nonamyloidogenic processing of the amyloid precursor protein, and increased phagocytosis and degradation of the amyloid-beta peptide [102,111]. Moreover, studies have shown that microglia respond rapidly to nerve lesions by migrating to the spinal projection territories of the central terminals of injured primary afferents, with subsequent proliferation, activation of p38 MAPK and ERK1/2, and production of proinflammatory cytokines and chemokines [114].…”
Section: Molecular Perspectivesmentioning
confidence: 99%
“…However, while P2Y6 receptors are coupled to G q /11 protein, P2Y14 receptors are coupled to G protein, and the increase in their expression is also related to the occurrence of peripheral nerve lesions, being regulated by p38 MAPK [114]. The activation of the P2Y6 receptors in microglia cells causes a rapid change in their morphology, with phagocytosis of damaged neurons being increased, through the reorganization of actin by a pathway mediated by the activation of protein kinase C (PKC) and PCL linked to the increase of intracellular Ca 2+ [94].…”
Section: Molecular Perspectivesmentioning
confidence: 99%
“…A large persuasive literature has implicated these receptors as primary activators of glia, particularly microglia, leading to the spinal release of a plethora of proinflammatory proteins and cytokines relevant to initiating facilitated pain states [367][368][369][370][371]. Intrathecal delivery of a variety of P2X and P2Y inhibitors results in a temporary reversal of hyperpathia after nerve injury [372][373][374][375]. Studies with a variety of approaches have strongly implicated the P2X4 subtype in spinal facilitation initiated by tissue and nerve injury [376].…”
Section: Purine Agonist/antagonistsmentioning
confidence: 99%